2019
DOI: 10.1371/journal.pntd.0007508
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perceptions and experiences of trachoma among Maasai in Tanzania: Implications for prevention and control

Abstract: Background The Alliance for the Global Elimination of Trachoma has set the target for eliminating trachoma as a public health problem by 2020. However, challenges remain, including socio-cultural issues. Districts in Northern Tanzania, predominantly inhabited by the Maasai ethnic group, remain endemic for trachoma. We explored socio-cultural factors that may impact the elimination of trachoma. Methods/Findings This study was nested within a larger ethnographic study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…However, conscious efforts have not been made to evaluate how different groups of citizens (rural, peri urban and urban dwellers) are coping with the proposed measures to prevent the disease. Several studies that sought to investigate the awareness, perceptions and attitudes of rural dwellers towards 4 diseases have proven to be useful for this study (Merga and Alemayehu 2015;Mtuy et al 2019;Workneh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, conscious efforts have not been made to evaluate how different groups of citizens (rural, peri urban and urban dwellers) are coping with the proposed measures to prevent the disease. Several studies that sought to investigate the awareness, perceptions and attitudes of rural dwellers towards 4 diseases have proven to be useful for this study (Merga and Alemayehu 2015;Mtuy et al 2019;Workneh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the literature search identified nine articles describing East African MMP motivations for moving, attitudes towards healthcare, and access to health services [ 14 , 15 , 17 – 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…An additional four studies illustrated low levels of engagement in healthcare services due to distrust of western medicine or misinformation about health service campaigns. Consequently, studies observed worse health outcomes in the MMPs, such as increased burden of malaria and trachoma [ 15 , 20 – 22 ]. In contrast, one study comparing health issues of settled and nomadic Turkana in Kenya reported that the settled Turkana suffered from higher rates of infections like eye infections, colds, coughs, and respiratory infections than the nomadic Turkana [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations